2022
DOI: 10.1007/s10875-022-01355-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Antibody Response to SARS-CoV-2 in Children

Abstract: Almost 2 years into the pandemic and with vaccination of children significantly lagging behind adults, long-term pediatric humoral immune responses to SARS-CoV-2 are understudied. The C19.CHILD Hamburg (COVID-19 Child Health Investigation of Latent Disease) Study is a prospective cohort study designed to identify and follow up children and their household contacts infected in the early 2020 first wave of SARS-CoV-2. We screened 6113 children < 18 years by nasopharyngeal swab-PCR in a low-incidence setting a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The C19.CHILD Hamburg study found that antibody titers amongst the pediatric cohort were 1.75 ( p < 0.001) times higher 90 days, 1.38 ( p =0.01) higher 180 days, and 1.54, ( p =0.001) times higher 270 days after infection than in the adult cohort. Results may be extrapolatable to postvaccine outcomes, as many vaccines rely on an attenuated virus or sequence from ancestral DNA [ 41 ]. Children between the age of 0–9 years are less likely to transmit the infection to a household member compared to adults, while adolescents seemingly exhibit a higher potential [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The C19.CHILD Hamburg study found that antibody titers amongst the pediatric cohort were 1.75 ( p < 0.001) times higher 90 days, 1.38 ( p =0.01) higher 180 days, and 1.54, ( p =0.001) times higher 270 days after infection than in the adult cohort. Results may be extrapolatable to postvaccine outcomes, as many vaccines rely on an attenuated virus or sequence from ancestral DNA [ 41 ]. Children between the age of 0–9 years are less likely to transmit the infection to a household member compared to adults, while adolescents seemingly exhibit a higher potential [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Ciao Corona study is one of the few large longitudinal studies in children and adolescents 24 , 25 , 63 . We were able to capture the time periods of the circulation of major SARS-CoV-2 variants (Wildtype, Delta, and Omicron BA.1) during our five testing rounds between June 2020 and July 2022.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the infection is often limited to the upper airway due to the predominant stimulation of an innate interferon-based immune response. This means that seroconversion may be lower and the disease induced by SARS-CoV-2 may be milder [ 42 ]. Older children may be able to produce antibodies above the threshold needed for MIS-C initiation [ 31 ].…”
Section: What Is Contributing To the Change In Mis-c Features Over Time?mentioning
confidence: 99%
“…One study found that only 13% of SARS-CoV-2 patients lost their IgG titers after 10 months, meaning that most patients still have detectable titers at the start of the following winter [ 50 ]. In children, titers after natural infection have been detectable for up to 9 months [ 42 ]. The presence of pre-existing memory in B cells that produce antibodies with sufficient affinity suggests that children may have a certain degree of tolerance to MIS-C, possibly due to a significant concentration of preformed antibodies.…”
Section: What Is Contributing To the Change In Mis-c Features Over Time?mentioning
confidence: 99%